Job Search Behaviour and Job Search Success of the Unemployed - Rainer Eppel; Helmut Mahringer; Andrea Weber (Austrian Institute of Economic Research (WIFO), 2014)
We combine information from a job-seeker survey and two sources of administrative data to shed light on the job search behaviour and job search success of the unemployed. Our particular focus is on the way the Public Employment Service (AMS) shapes job search effort and outcomes in terms of the exit rate to work and of post-unemployment job match quality. Job-seekers attach a high value to internet job search, but social networks are by far the most promising job search channel. The AMS has a central role in the job search process of the unemployed, particularly for job-seekers with low education and long unemployment record. We find a positive link between the amount of AMS counselling and job search effort. Our results indicate that the AMS is effective in facilitating exit from unemployment to paid work - directly, through placing of jobs and increasing the efficiency of job search, as well as indirectly, by stimulating job search effort. The jobs placed by this intermediary do not significantly differ in job tenure from those generated by other channels, but they are rather poorly paid. After adjustment for differences in covariates, monthly starting wages are significantly lower for people placed via the AMS compared with those successful with the internet and private employment agencies.
Keywords: 330; Job search; Public employment service; Job match quality